Teucrium amplexicaule (Lamiaceae), a neglected name for a Spanish endemic - Crespo, Manuel B.; Alonso, Ma Ángeles; Martínez-Azorín, Mario (Phytotaxa, 2017)
Lamiaceae is one of the most diversified families in the Mediterranean basin. In particular, the Iberian Peninsula and Northern Africa concentrate about one third of the described taxa (Greuter & al. 1989, Navarro & al. 2002), many of which are endemics with very narrow distribution areas.